In vivo MAPK reporting reveals the heterogeneity in tumoral selection of resistance to RAF inhibitors - Basile, Kevin J. (2013)
Activation of the ERK1/2 mitogen-activated protein kinases (MAPKs) confers resistance to the RAF inhibitors vemurafenib and dabrafenib in mutant BRAF-driven melanomas. Methods to understand how resistance develops are important to optimize the clinical utility of RAF inhibitors in patients. Here we report the development of a novel ERK1/2 reporter system that provides a non-invasive, quantitative and temporal analysis of RAF inhibitor efficacy in vivo. Use of this system revealed heterogeneity in the level of ERK1/2 reactivation associated with acquired resistance to RAF inhibition. We identified several distinct novel and known molecular changes in resistant tumors emerging from treatment-naïve cell populations including BRAF V600E variants and HRAS mutation, both of which were required and sufficient for ERK1/2 reactivation and drug resistance. Our work offers an advance in understanding RAF inhibitor resistance and the heterogeneity in resistance mechanisms, which emerge from a malignant cell population.